Mild and efficient cyanuric chloride catalyzed Pictet–Spengler reaction - Sharma, Ashish; Singh, Mrityunjay; Rai, Nitya Nand; Sawant, Devesh (Beilstein Journal of Organic Chemistry, 2013)
A practical, mild and efficient protocol for the Pictet–Spengler reaction catalyzed by cyanuric chloride (trichloro-1,3,5-triazine, TCT) is described. The 6-endo cyclization of tryptophan/tryptamine and modified Pictet–Spengler substrates with both electron-withdrawing and electron-donating aldehydes was carried out by using a catalytic amount of TCT (10 mol %) in DMSO under a nitrogen atmosphere. TCT catalyzed the Pictet–Spengler reaction involving electron-donating aldehydes in excellent yield. Thus, it has a distinct advantage over the existing methodologies where electron-donating aldehydes failed to undergo 6-endo cyclization. Our methodology provided broad substrate scope and diversity. This is indeed the first report of the use of TCT as a catalyst for the Pictet–Spengler reaction.
Keywords: β-carboline; cyanuric chloride; 6-endo cyclization; Pictet–Spengler; TCT